Interaksi Komunikasi dan Konsep Diri Pengungsi Etnis Rohingya di Kota Medan - Azhar Saputra; Iskandar Zulkarnain; Dewi Kurniawati (PERSPEKTIF, 2023)
The research aims to analyze the interaction communication and self-concept of Rohingya refugees in Medan. This research conducted using qualitative and descriptive approach. Data are collected using interviews and observation. The research subjects are determined using purposive technique. Data are analysed using Miles and Huberman interactive model. The result obtained from this research indicate that the interaction done by Rohingya refugees in Medan creates communication experience for them which are divided into 2 categories, namely enjoyable communication experiences such as acceptance, symphaty, friendship, affection, and support; and unenjoyable communication experience such as anxiety, labelling, restrictions, and misscommunication. Self-concept of Rohingya refugees in Medan reflected into dimensionsof self-concept namely knowledge, expectation, and evaluation. Nine out of twelve informants have positive self-concept which can be seen from the small gap between the dimension of future self-expectationsthat leads to acceptance on their recent personal condition. While the other three informants have negative self-concept which can be seen from the considerable dap between the dimension of knowledge and future self-expectation regarrding thet leads to rejection on their recent personal condition.